Structural equation model of variables influencing Thai ceramics entrepreneur organisational sustainability - Phainphin Kowuttiphong; Wanno Fongsuwan (My University, 2018)
The ceramics industry is vital to the economy of Thailand which globally, has been projected to reach $US705 billion by 2025. Traditionally however, for centuries the ceramics industry has been clustered in regional enclaves centred on small, entrepreneurial enterprises. This paper therefore investigated a multitude of factors including trade regulations, global competition, quality concerns, speed of development processes and production, and lack of branding and innovation, to determine the factors affecting organisational sustainability of ceramic enterprises. From the 280 Thai enterprises surveyed and analysed by use of a structural equation model by PLS-graph software it was determined that organisational performance affects organisational sustainability to the greatest extent due to monetary and non-monetary factors with an intermediate input into innovation, the business environment and business strategies. Organisational performance is also influenced by innovation and business strategies.
Keywords: Multitude; International Business and FDI